Serum Oxytocin Level Correlates With Gut Microbiome Dysbiosis in Children With Autism Spectrum Disorder - Huang, Minshi; Liu, Kevin; Wei, Zhen; Feng, Zhe; Chen, Jierong; Yang, Jie; Zhong, Qin; Wan, Guobin; Kong, Xue-Jun (Frontiers in Neuroscience, 2021)
To investigate the levels of serum oxytocin (OT) in children with autism spectrum disorder (ASD) and explore the association between OT levels and gut microbiota relative abundances, we recruited 39 children with ASD children–mother dyads and 44 healthy controls. Serum OT levels were determined via enzyme-linked immunosorbent assay and gut microbiota abundances were determined by 16S rRNA sequencing. We found that the OT level of ASD was lower than the healthy control group overall (P < 0.05). Furthermore, we present preliminary evidence of gut microbiome dysbiosis observed among children with ASD to lower levels of OT based on correlational analysis between serum OT and specific gut microbiota abundances (P < 0.05). We also found sex-related differences in serum OT levels and GIS index (P < 0.05). However, the generalizability of findings relevant to females with ASD require further validation in future studies involving larger sample sizes and balanced sex distributions due to the small number of females involved in this study. Nonetheless, these new findings further our understanding of the effects of low serum OT levels among individuals with ASD, which provides preliminary evidence in hopes of guiding future study design or mechanistic studies. The findings of the present study may be suggestive of potential ASD subtypes based on ASD severity and gut microbiome composition that may facilitate the prediction of the therapeutic responses of OT among those with ASD.